PENGARUH DISIPLIN KERJA, JAMINAN SOSIAL, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PG. KEBON AGUNG MALANG - Kusuma Putri, Vitria Dewi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to find and analyze the influence of Work Discipline, Social Security and Work Environment on Employee Performance at PG. Kebon Agung Malang, this study is conducted by Partial and Dominant Test. This type of this study is Expanatory Research that describes a casual relationship between the variables through hypothesis testing.This study uses data sample by taking 80 respondents from a population of 335 permanent employees. The sampling uses probability sampling methods by simple random sampling technique and uses the slovin formula. While the data collection technique uses the technique of questionnaires, observations and review of related literature.To determine the magnitude of the relationship and the influence of the independent variables, it uses Multiple Linear Regression Analysis Model. Meanwhile, to test the hypothesis, it uses statistical tests.The results reveals that the statistic value of thitung test is greater than ttabel (1) Discipline Work (2,137> 1,992), Social Security (2.622> 1.992) and the Working Environment (2.433> 1.992) significantly affects to the employee performance (2) variable of Social Security has the most dominant influence to the employee performance (0317). The great contribution of all independent variables on the dependent variable in coefficients (R ²) amounted to 50.6% and the remaining 49.4% is explained by other factors which in not discussed in this study.Keywords: Work Discipline, Social Security, Work Environment, Employee Performance.